The Role of Sustainable Human Resources Management on the Effectiveness of the Organization an Analytical Study at the University of Anbar - saleh, saja; Yassin Rahim, Mohammed (Journal of Economics and Administrative Sciences, 2025)
This research aims to examine the influence that sustainable human resource management (HRM) has on organizational effectiveness at the university level. In view of that, the research debates sustainable HRM practices, such as selection, participation, and empowerment, which have a stake in the success of the institution by harmonizing employee development with the long-term goals of the organization. This study used a quantitative survey method to collect data from 169 university employees and analysis through the use of statistical techniques using SPSS.The outcome suggests that sustainable HRM positively and directly affects organizational effectiveness. The evidence supports employee empowerment as the most significant component, followed by participation and selection. Employees being involved in making decisions, developing their careers, and nurturing a sustainable work culture contribute to improved institutional performance. More importantly, the study pointed out that universities should create HR policies supportive of continuous development, environmental sustainability, and strategic workforce management.The research recommends that policies be enhanced for recruiting, training, and employee engagement so that university efficiency could become more long-term. Further, it highlights that universities should incorporate sustainable (HRM) practices to remain competitive, resilient, and in line with contemporary educational and environmental requirements. The research presents an important direction for academic institutions intending to have their performance improved through sustainable human capital strategies.